PREVALENCE AND RISK FACTORS OF IRON DEFICIENCY ANEMIA IN PRIMARY CARE SETTING IN LOW INCOME COUNTRIES : A COMPREHENSIVE SYSTEMATIC REVIEW - Raras Pambajeng, Cesil; Siskanondang Manalu, Ema Febianti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Children under the age of five are frequently affected by iron deficiency anemia. Iron deficiency affects children's psychomotor development and their cognitive ability. Aims : This systematic review is to review the prevalence and risk factors of iron deficiency anemia in low income countries. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, ScienceDirect and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 828 articles, whereas the results of our search on SAGEPUB brought up 1683 articles, our search on SCIENCE DIRECT brought up 2880 articles. The results of the search conducted for the last year of 2014 yielded a total 273 articles for PubMed, 630 articles for SAGEPUB and 1319 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 3 of which came from PubMed, 1 of which came from SAGEPUB and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, the global prevalence of iron insufficiency and iron deficiency anemia was noteworthy. To prevent complications, it is therefore necessary to regularly screen for and treat iron deficiency and iron deficiency anemia, especially in children who are considered high-risk.